A new meso-microscale coupled modelling framework for wind resource assessment: A validation study. (November 2020) - Durán, Pablo; Meiβner, Cathérine; Casso, Pau
Abstract: In this work the simulation results of a newly developed meso-microscale coupling methodology suited for steady-state computational fluid dynamic models (CFD) are compared with mesoscale and standalone microscale simulations at 5 sites. The coupling methodology uses averaged fields of wind speed and potential temperature simulated by the Weather Research and Forecasting model as boundary and initial conditions for the CFD model. In complex terrain, the coupled model reproduces the measured vertical profiles of horizontal wind speed better than the standalone microscale model or the mesoscale model. The coupled model also performs better in the horizontal extrapolation of measurements in complex terrain. In simpler terrain, it is beneficial to use the coupled model when the focus is on areas located downstream of even small terrain features. Otherwise, the mesoscale simulations perform as good or better than the coupled model. Highlights: A meso-icroscale coupling approach based on CFD is validated at five sites. The coupled model is compared with mesoscale and standalone CFD simulations. The coupled model outperforms the other modelling approaches in complex terrain. The coupled model reproduces better the wind shear than other modelling approaches. Low-level jets and horizontal wind turning are reproduced by the coupled model.